تأثير برنامج تعليمي باستخدام التمرينات التمثيلية والتنافسية على تعلم بعض المهارات الحركية الأساسية في ألعاب القوى للأطفال - هارون، وليد مصطفى (جامعة المنيا - كلية التربية الرياضية, 2019)
The research aimed at designing a suggested program by acting and competitive exercises on developing the basic kinetic skills on athletics for children of grade one. The experimental method was followed by using the experimental design for two equal and equivalent groups, one is experimental using the suggested program and the other is control using the traditional program on a sample of (60) from grade one students at Saft Alkhamar primary school (l) - Minia governorate. Distribution normality and equivalence between them was found in some age variables (age - height -weight - intelligence) and physical and skillful tests... Tests, opinion survey and the suggested program are one of the most important tools for collecting data. The most important results revealed that the suggested program by using acting and competitive exercises affected positively on developing the basic kinetic skills on athletics for children of grade one of the experimental group. Also the conventional program affected positively on developing the basic kinetic skills on athletics for children of grade one of the control group. The suggested program by using acting and competitive exercises affected positively than the traditional one on developing the basic kinetic skills on Athletics for children (in question).
Keywords: التربية الرياضية -- اللياقة البدنية -- المهارات الحركية -- ألعاب القوى